Effectiveness of 3D poster in improving menstrual hygiene knowledge among adolescent girls: A quasi-experimental study - Rani Mustikawati; Windi Chusniah Rachmawati; Endang Sri Redjeki; Nurnaningsih Herya Ulfah (CV Rezki Media, 2025)
Background: Personal hygiene during menstruation is important and must be applied during the menstrual cycle. Suppose personal hygiene during menstruation is not maintained correctly. In that case, adolescent girls have the potential to experience health problems such as vaginal discharge, irritation of the genital area, allergies, inflammation, and Urinary Tract Infection (UTI). As many as 75% of women in Indonesia have experienced vaginal discharge once, while 45% have experienced it more than 2 times. Objectives: This study aimed to determine the effectiveness of 3D posters in increasing knowledge about personal hygiene during menstruation. Methods: The research method used was Research and Development (R&D), which was conducted through a pre-experimental approach with one group pretest-posttest. Ninety-five adolescent girls in class VII of State Junior High School 13 Malang participated in the study obtained using a purposive sampling technique. The research instrument used a closed-type questionnaire with 10 items to measure knowledge. Results: The 3D poster product obtained a percentage value of media feasibility of 95% for the media aspect and 92% for the material aspect, which means it is very feasible to use. After the intervention, it is known that there is an effect of providing health education using 3D posters on the knowledge of adolescent girls regarding personal hygiene during menstruation according to the p-value = 0.000 from the Wilcoxon test. Conclusions: Personal hygiene education during menstruation should be done more often to improve the knowledge of adolescent girls. The findings support the use of 3D media in menstrual health promotion, especially in schools with limited resources.